2018
DOI: 10.1111/zph.12538
|View full text |Cite
|
Sign up to set email alerts
|

Frequent human‐poultry interactions and low prevalence of Salmonella in backyard chicken flocks in Massachusetts

Abstract: The backyard chicken (BYC) movement in the USA has increased human contact with poultry and subsequently, human contact with the pathogen Salmonella. However, to date, there have been few studies assessing prevalence of Salmonella in backyard flocks, despite the known public health risk this zoonotic bacterium poses. The objective of this study was to characterize human‐BYC interactions and assess the prevalence of Salmonella among BYC flocks. We interviewed 50 BYC owners using a structured questionnaire to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Due to the risk of Salmonella transmission associated with the handling of live poultry, a few studies have assessed the prevalence of this pathogen in backyard poultry in the USA (Anonymous, 2016;Basler et al, 2016;Clothier, Kim, Mete, & Hill, 2018;McDonagh et al, 2019). Additionally, a few published studies have reported that other opportunistic pathogens including Escherichia coli and other non-fermenting Gram-negative bacteria (GNB) such as Acinetobacter spp., Achromobacter spp.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the risk of Salmonella transmission associated with the handling of live poultry, a few studies have assessed the prevalence of this pathogen in backyard poultry in the USA (Anonymous, 2016;Basler et al, 2016;Clothier, Kim, Mete, & Hill, 2018;McDonagh et al, 2019). Additionally, a few published studies have reported that other opportunistic pathogens including Escherichia coli and other non-fermenting Gram-negative bacteria (GNB) such as Acinetobacter spp., Achromobacter spp.…”
Section: Introductionmentioning
confidence: 99%
“…Backyard poultry and small pastured swine are animal production systems that have been increasing in popularity (Bailey & Larson, ; Beam, Garber, Sakugawa, & Kopral, ; Weiss, ). While most backyard chickens are raised as pets and for home egg consumption (Elkhorabi, Blatchford, Pitesky, & Mench, ; McDonagh et al, ), the backyard ownership of domestic swine is mainly limited to meat production (Fournier, ).…”
Section: Introductionmentioning
confidence: 99%
“…Another important characteristic to highlight is that, of the surveyed BPS, those in charge of maintaining them were mainly pensioners (older than 60 years); a situation that has been reported previously [7]. In Chile, this could be a factor that influences the lack of, or delay in, the adoption of new practices that could improve the sanitary status of these productive systems [69]. There is also a perception of mistrust in those in charge of BPS directed towards official veterinary and health authorities, which is reflected in the low participation rate of these entities in the visited BPS.…”
Section: Bps Management Characterizationmentioning
confidence: 99%